Remarks on vacuum state and uniqueness of concentration process - Vladimir G. Danilov (Electronic Journal of Differential Equations, 2008)
We give two examples of nonuniqueness of generalized solutions of pressureless gas dynamics systems. In both of these examples, the presence of the Dirac delta-function leads to nonuniqueness.